Mitochondrial genome study in blood of maternally inherited ALS cases - Brockmann, Sarah J.; Buck, Eva; Casoli, Tiziana; Meirelles, João L.; Ruf, Wolfgang P.; Fabbietti, Paolo; Holzmann, Karlheinz; Weishaupt, Jochen H.; Ludolph, Albert C.; Conti, Fiorenzo; Danzer, Karin M. (Human genomics, 2023)
ALS is a heterogeneous disease in which different factors such as mitochondrial phenotypes act in combination with a genetic predisposition. This study addresses the question of whether homoplasmic (total mitochondrial genome of a sample is affected) and/or heteroplasmic mutations (wildtype and mutant mitochondrial DNA molecules coexist) might play a role in familial ALS. Blood was drawn from familial ALS patients with a possible maternal pattern of inheritance according to their pedigrees, which was compared to blood of ALS patients without maternal association as well as age-matched controls. In two cohorts, we analyzed the mitochondrial genome from whole blood or isolated white blood cells and platelets using a resequencing microarray (Affymetrix MitoChip v2.0) that is able to detect homoplasmic and heteroplasmic mitochondrial DNA mutations and allows the assessment of low-level heteroplasmy. We identified an increase in homoplasmic ND5 mutations, a subunit of respiratory chain complex I, in whole blood of ALS patients that allowed maternal inheritance. This effect was more pronounced in patients with bulbar onset. Heteroplasmic mutations were significantly increased in different mitochondrial genes in platelets of patients with possible maternal inheritance. No increase of low-level heteroplasmy was found in maternal ALS patients. Our results indicate a contribution of homoplasmic ND5 mutations to maternally associated ALS with bulbar onset. Therefore, it might be conceivable that specific maternally transmitted rather than randomly acquired mitochondrial DNA mutations might contribute to the disease process. This stands in contrast with observations from Alzheimer’s and Parkinson’s diseases showing an age-dependent accumulation of unspecific mutations in mitochondrial DNA.
Gesehen am 19.06.2024